Inflammatory microenvironment in ARDS patients polarize clinically utilized MSCs towards a pro-inflammatory MSC phenotype - Enes, S. Rolandsson; McKenna, D.; dos Santos, C.; Liu, K.D.; Rocco, P.R.; Matthay, M.; Weiss, D.J. (Cytotherapy (Oxford, England), 2020)
Despite an enormous interest in using MSCs as a cell-based therapy to treat acute respiratory distress syndrome (ARDS), the knowledge of MSC in vivo mechanism of actions are limited. ARDS pathology is driven by an acute severe inflammatory response, but how this inflammatory environment influences MSC behavior is not yet well understood and needs to be extensively studied. Clinically utilized bone marrow-derived human MSCs were exposed to bronchoalveolar lavage fluids (BALF), a surrogate for the in vivo environment, obtained from patients with ARDS or from healthy control subjects (HC). Following exposure, cells and conditioned medium were assessed for different factors including viability, levels of pro- and anti-inflammatory cytokines, and mitochondrial activity. Following 24 hours exposure, we found that there were no differences in viability in ARDS BALF-exposed MSCs compared to HC or saline-exposed cells. However, preliminary data indicate that MSCs exposed to ARDS BALF differentiated towards a more pro-inflammatory phenotype with significant increased production of pro-inflammatory mediators such as IL-6, IL-8, and IL-18 compared to saline exposed MSCs. A trend towards increased secretion was also seen in production of IL-6 and IL-8 in ARDS BALF-exposed MSCs compared to HC BALF-exposed cells, however this did not reach significance. Interestingly, a significant increase in HGF was observed in ARDS BALF-exposed MSCs compared to saline control. Furthermore, preliminary metabolomics analysis suggests that MSCs exposed to BALF samples from both ARDS and HC subjects had an altered mitochondrial activity compared to unstimulated MSCs. Our data suggest that the inflammatory environment found in ARDS patients activate and polarize MSCs towards a pro-inflammatory phenotype. These results further highlight the need to understand the effect of the in vivo inflammatory environment on systemic or locally administered MSCs.